Some Peasant Poets - Kezich, Giovanni (Peter Lang AG, 2013)
This is an eccentric book in the best possible sense: an ethnography that began outside the walls of the academic fortress, in personal curiosity allied with the fashionable militancy of its early 1970’s inception and then developed with an eye to competing theories and practices about folklore and oral literature. The author spent fifteen years studying the ‘peasant poets’ of Tolfa in Latium (Central Italy), closely following the lives, performance practices and general environmental and life-situations of a group of poets of peasant background who engage in public poetic contests in their area. Extemporising around an odd mixture of sixteenth-century and contemporary themes in an archaic style, they sustain a literary subculture that is all their own. Some Peasant Poets is a fascinating ‘working diagram’ of how the machinery of culture operates, of how cultural discourses are engineered by various petty proprietors divided, as in the author’s peasant city of Tolfa, into rival poetry circles battling for attention, prestige and funding. The importance of the book is in its close dissection of these cultural mechanisms notwithstanding the somewhat bizarre and archaic materia and style of its practitioners, the peasant poets of Latium.
10.3726/978-3-0351-0556-8
Keywords: Volkslyrik; Mündliche Literatur